Valuation and musealization of the heritage in urban environment: the case of public murals paintings of Lisbon (Cadernos de Sociomuseologia, 2015)
Understanding the function of museology, as a process of transmission of knowledge, heritage and collective memories, rewarding communication. Today, in a constant process of globalization, with new technologies in expansion, the challenge of adapting policies and museological practices into interdisciplinary museology, comprising the valences of new information technologies (ICT) in favor of Sociomuseology. In this article, one relates museology with mural heritage, based on first identifying the mural  sites and buildings where they are located. One intends to analyze its history, authors and  architects, commissioners, and the sociocultural environment that prevailed in the city of  Lisbon (Portugal) during “Estado Novo”, and with particular historical and museological  relevance. To provide knowledge for wall art and the understanding of its role in today's society, contextualizing it at the time it was executed. To interpret the symbolism and socio-cultural importance that the murals had at the time of “Estado Novo” and today. To analyze the ideological significance of public spaces and realize the "sacralized" the "desecrated" process space. It is, therefore, important to provide answers to the following research questions: • How important is to musealize the mural heritage of Lisbon? • What symbols carry these murals? • What is the ideological significance of Public Spaces? • What advantages can new technologies bring to Museology? Keywords: Museology and communication; Heritage; Mural Paintings; Symbology; Public Spaces.